PENILAIAN KINERJA EMBUNG HALIWEN BERDASARKAN KRITERIA PEMELIHARAAN EMBUNG IRIGASI - Melchior Bria; Sutirto Sutirto; Anastasia H. Muda (Politeknik Negeri Jakarta, 2018)
ABSTRACTThis research aims to determine how high the level of effectiveness, how the level of service and how the satisfaction of Pedestrian Bridge (PB) users in the Market Kramat Jati. Observations were made by calculating the volume of crossers using and not using the PB as well as the volume of vehicles passing during the morning rush hour and afternoon peak hours both on weekdays and on holidays. This data is used as the basis for the analysis of the effectiveness and determination of the appropriate type of crossing facilities. The observation of the user time of PB with the sample of 29 people for each observation time. Data collection also used questionnaires to 53 PB user respondents containing questions relating to the physical components of PB and supporting data that became the basic variables of consideration for the use of PB. The effectiveness analysis result shows that the JPO is not effective at the service level including category A. Based on the user satisfaction analysis, 59% are satisfied and very satisfied using the PB with the age range of 21-30 years old, the high school education, the most self employed, the monthly income 1 -3 million, the frequency of work usage < 2x per day, from destination to shopping / market with the intention to work.Keywords: Effectiveness, Pedestrian Bridge, User Satisfaction, Level Of Service.ABSTRAKEmbung Haliwen merupakan salah satu Embung Irigasi andalan di Kabupaten Belu dan melayani masyarakat Desa Sirani untuk keperluan irigasi untuk tanaman pengolahan tanaman padi. Untuk itu perlu dipertahankan keberlanjutannya sehingga dapat memberikan manfaat bagi masyarakat sekitar. Penelitian ini dimaksudkan untuk menilai kinerja embung Haliwen berdasarkan Kriteria Pemeliharaan Embung Irigasi. Penilain dilakukan dengan cara emberi bobot pada kriteria, kemudian dari nilai bobot tersebut dirata-rata untuk mendapatkan bobot keseluruhan. Adapun kriteria yang dimaksud adalah Stabilitas Struktur, Kriteria Fisik dan Lingkungan, Kriteria Eknomi/Fnansial, Kriteria Kebijakan Pemerintah, dan Kriteria Sosial Budaya. Hasil penelitian menunjukkan bahwa rata-rata nilai kinerja Embung Haliwen ada pada kisaran 3,41, sehingga dapat dikatakan dalam kategori Cukup. Hal ini berarti kinerja embung irigasi Haliwen perlu ditingkatkan lagi guna menjamin keberlanjutan system irigasi menggunakan air adri embung Haliwen.Kata Kunci : Kinerja, Embung, Irigasi, Pemeliharaan